Effects of Cervical Spine Mobilization on Respiratory Function and Cervical Angles of Stroke Patients: A Pilot Study - An, Ho Jung (Healthcare (Basel), 2021)
The forward head posture (FHP) of stroke patients has a negative impact on respiratory function. Cervical spine mobilization is a manual therapy technique that used to prevent and treat FHP and respiratory function. This pilot study investigated whether cervical spine mobilization can effectively improve outcomes following FHP and respiratory function of stroke patients. Twenty-four patients participated in our assessor-blinded randomized controlled trial. All the participants received neurodevelopmental treatments (gait training and trunk rehabilitation). The experimental group additionally received 15-min sessions of cervical spine mobilization three times per week for 4 weeks. The control group received cervical spine sham mobilization during the same period. For the cervical angles, the cranial vertebral angle (CVA) and cranial rotation angle (CRA) were measured. A respiratory function test was performed to measure the forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), peak expiratory flow (PEF), maximal inspiratory pressure (MIP), maximal expiratory pressure (MEP), and chest circumferences (upper and lower chest sizes). Except for MIP, there was no significant difference between the experimental group and the control group. The CVA and CRA were significantly increased in the experimental group only. Cervical spine mobilization improved cervical angles and inspiratory function of the stroke patients in this study. However, a comparative study with a larger number of patients is needed to confirm this finding from our pilot study, which had a small sample size.